Bituin the distance a multimodal campaign that aims to bridge the communication gap betweeen parenting Overseas Filipino Workers (OFW) and their left-at-home children aged 7 to 11 years old - Banday, Rafael Joy F.; Austria, Romanlito S. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
After the Martial Law, Marcos administration saw itself plagued with the ballooning unemployment rate because the domestic economy could not generate enough sustainable local jobs. Because of this, the migration of Filipino workers was seen as a temporary solution to the country's increasing foreign debt during the late 90s. Republic Act 8042, most commonly known as the Migrant Workers and Overseas Filipinos Act of 1995 provided the institution the policies of overseas employment and established a higher standard of protection and promotion of the welfare of migrant workers, their families and overseas Filipinos.

One product of this phenomenon is long-distance parenting. Long-distance parenting has become a prevalent phenomenon due to worker migration, as parents leave their homes in search of better job opportunities and financial stability. This migration, however, can have a significant impact on the psychosocial development of their adolescent children. Research has shown that long distance parenting can lead to increased feelings of isolation, abandonment, and emotional distress among children. Studied have also shown that long distance parenting can lead to a lack of communication and emotional distance between the parent and child, which can have a negative impact on the child's psychosocial development.

The objective of this campaign is to bridge the communication gap between parenting Overseas Filipino Workers (OFWs) and their left-at-home adolescent children. By utilizing various communication channels and creative strategies, the campaign aims to strengthen the parent-child relationship, foster understanding, and provide emotional support during the separation.
Thesis (Bachelor of Fine Arts in Visual Communication) -- University of the Philippines Diliman
Bibliography: leaves 283-285
Keywords: Parent and child; Parenting; Overseas Filipino Workers (OFW); Parent and child -- Communication